2017
DOI: 10.3389/fpsyg.2017.01314
|View full text |Cite
|
Sign up to set email alerts
|

Dispelling the Myth: Training in Education or Neuroscience Decreases but Does Not Eliminate Beliefs in Neuromyths

Abstract: Neuromyths are misconceptions about brain research and its application to education and learning. Previous research has shown that these myths may be quite pervasive among educators, but less is known about how these rates compare to the general public or to individuals who have more exposure to neuroscience. This study is the first to use a large sample from the United States to compare the prevalence and predictors of neuromyths among educators, the general public, and individuals with high neuroscience expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
238
2
33

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(293 citation statements)
references
References 51 publications
(80 reference statements)
20
238
2
33
Order By: Relevance
“…Although there is some evidence that those with significantly more expert knowledge of the brain are less likely to believe in neuromyths (Howard‐Jones et al, ; MacDonald et al, ), this is not a consistent finding. In their study of in‐service teachers, Dekker et al () found that an interest in the brain made belief in neuromyths more likely, possibly due to the increased likelihood of encountering more dubious claims.…”
Section: Teachers' Beliefs In Neuromythsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although there is some evidence that those with significantly more expert knowledge of the brain are less likely to believe in neuromyths (Howard‐Jones et al, ; MacDonald et al, ), this is not a consistent finding. In their study of in‐service teachers, Dekker et al () found that an interest in the brain made belief in neuromyths more likely, possibly due to the increased likelihood of encountering more dubious claims.…”
Section: Teachers' Beliefs In Neuromythsmentioning
confidence: 98%
“…There is a growing body of literature documenting the neuromyths found commonly and widely among in‐service teachers with studies in the United Kingdom and Netherlands (Dekker, Lee, Howard‐Jones, & Jolles, ), East China (Pei, Howard‐Jones, Zhang, Liu, & Jin, ), Greece (Deligiannidi & Howard‐Jones, 2015), Turkey (Karakus, Howard‐Jones, & Jay, ), Latin America (Gleichgerrcht, Lira Luttges, Salvarezza, & Campos, ; Spain (Ferrero, Garaizar, & Vadillo, , Canada (Sarrasin, Riopel, & Masson, ), Switzerland (Tardif et al, ), the United States (MacDonald et al, ), and South Korea (Im, Cho, Dubinsky, & Varma, ). The most prevalent neuromyths have been remarkably consistent across countries, with widespread beliefs that teaching should be tailored according to a pupil ' s learning style and that cerebral hemispheric dominance explains differences between learners.…”
Section: Teachers' Beliefs In Neuromythsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while it may be difficult to verify the precise content of the courses in initial teacher training, it may be judicious to ensure that course descriptors and textbooks provide content in accordance with current knowledge. Finally, the introduction of neuroeducation courses in initial training, including the refutation of certain neuromyths (see Kowalski & Taylor, ; Macdonald, Germine, Anderson, Christodoulou, & McGrath, ), could constitute a part of an interesting solution. These solutions could ultimately allow teachers to be aware of these neuromyths, could prevent them from emerging, dispel those already present in education, and help move towards an education increasingly based on research.…”
Section: Discussionmentioning
confidence: 99%
“…When teachers and students receive instruction on the neuroscience of learning, teachers’ pedagogy and students’ school performance and attitudes towards learning improve (Blackwell et al 2007; Dubinsky 2010; Dubinsky et al 2013). As these ideas drive neuroscience teaching to become more widespread, designing approaches to handle misconceptions will be critical for preventing the creation and spread of new neuromyths (Macdonald, Germine, Anderson, Christodoulou & McGrath 2017). …”
Section: Future Directionsmentioning
confidence: 99%